Self-Healing and Wide Temperature-Tolerant Cellulose-Based Eutectogels for Reversible Humidity Detection - Wu, Yufang (Langmuir : the ACS journal of surfaces and colloids, 2024)
A kind of ionic conductive gel (also named eutectogel) is developed from an inorganic salt (ZnCl2)-based deep eutectic solvent (DES). The ternary DES consists of ZnCl2, acrylic acid, and water, and cotton linter cellulose is introduced into the DES system to tailor its mechanical and conductive properties. Enabled by the extensive hydrogen bonds and ion-dipole interactions, the obtained eutectogel displays superior ionic conductivity (0.33 S/m), high stretchability (up to 2050%), large tensile strength (1.82 MPa), and wide temperature tolerance (-40 to 60 °C). In particular, the water-induced coordination interactions can tune the strength of hydrogen/ionic bonds in the eutectogels, imparting them with appealing humidity sensing ability in complex and extreme conditions